Enhancing Learning Outcomes in Garments Trade: A Needs-based Intervention Approach for Students - , Mylene D. Calaranan; , Brian Jay Corpuz (Archives of Current Research International, 2023)
The study focused on the development and validation of Strategic Intervention Materials (SIMs) to enhance the least mastered skills of Grade 10 Garments Trades students. It covered topics on Sewing Machine Operations, Preparation and Cutting of Materials and Assembling the Blouse and Skirts. The Strategic Intervention Materials were validated by five (5) technical experts.. A 5-point rubric scale and interpretation based on the Standard criteria issued by the Department of Education (DepEd) Bureau of Secondary Education in 2005 was used in rating the materials. Descriptive statistics, particularly frequencies, percentages and means were used in the analysis and interpretation of data. The study was conducted at the Ilocos Norte College of Arts and Trades (INCAT) in Laoag City. This research employed universal sampling. The Grade 10students specializing in Garments Trades of INCAT for the school years 2013-2014, 2014-2015 and 2015-16 were used as respondents for the first phase of the study to analyze their least mastered competencies based on the results of their NC II certification. The sample consisted of 238 students, purely females, who are enrolled in Garments Trade for school years 2013-2014 (73 students), 2014-2015 (100 students) and 2015-2016 (65 students). Results of experts’ validation and evaluation revealed that the guide card, activity card, assessment card, enrichment card and reference card of three SIMs developed were found to be valid. The developed SIMs have met the standards set by DepEd in developing such materials and are valid to enhance students least mastered skills along Garments Trade.